Ionic MOFs (Metal-Organic Frameworks) catalyst with anion guest wrapped by electropositive framework

By grafting ionic liquid on sUiO-66-NH2, an ionic MOFs catalyst with a positively charged frame wrapped in anionic guest was prepared, which solved the problems of long epoxide-CO2 cycloaddition reaction time and low catalytic efficiency in the prior art, and achieved efficient and stable catalytic effect.

CN119819374AActive Publication Date: 2025-04-15FUZHOU UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510098116.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-22
Publication Date
2025-04-15
Estimated Expiration
2045-01-22

AI Technical Summary

Technical Problem

The existing MOFs-based catalysts have a long reaction time in catalyzed epoxide-CO2 cycloaddition reaction, and have low catalytic efficiency for epoxides with steric hindrance and electron-rich groups such as styrene oxide.

Method used

An ionic MOFs catalyst that encapsulates anionic guest using a positive electrical frame is formed by grafting the ionic liquid chemical bond onto sUiO-66-NH2 to form a multifunctional heterogeneous catalyst for catalyzing the epoxide-CO2 cycloaddition reaction.

Benefits of technology

The high activity and stability of catalyzed epoxide-CO2 cycloaddition reaction under the condition of no promoter is achieved, which shortens the reaction time and significantly improves the catalytic efficiency of a variety of epoxides, including styrene oxidation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119819374A_ABST
    Figure CN119819374A_ABST
Patent Text Reader

Abstract

The invention discloses an ionic MOFs catalyst with an anion guest wrapped by an electropositive framework and application of the ionic MOFs catalyst, and belongs to the technical field of composite material synthesis. According to the preparation method, an MOFs carrier sUiO-66-NH2 is prepared through a hydrothermal method, triethylene diamine and bromide ions are introduced through post-synthesis modification, and the ionic MOFs catalyst with an anion guest wrapped by an electropositive framework is prepared. The sUiO-66-NH2 is used for immobilizing the ionic liquid, so that the sUiO-66-NH2 has CO2 adsorption and activation capacities at the same time, and can enable epoxide to be subjected to ring opening, therefore, the sUiO-66-NH2 can be used as a multifunctional heterogeneous catalyst to be applied to catalysis of epoxide-CO2 cycloaddition reaction to prepare cyclic carbonate, and a cocatalyst and a solvent do not need to be additionally added in a reaction system.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of composite material synthesis, and specifically relates to an ionic MOFs catalyst with a positively charged framework encapsulating an anionic guest and an application of the catalyst in catalyzing an epoxide-CO2 cycloaddition reaction to prepare a cyclic carbonate. Background Art

[0002] Carbon dioxide (CO2) is not only a major greenhouse gas, but also a rich, green, non-toxic and renewable C1 raw material. In recent years, excessive CO2 emissions have further exacerbated environmental problems such as global warming, melting glaciers and rising sea levels, making the world environment face greater challenges. Therefore, from the dual perspectives of environmental protection and resource utilization, chemical fixation and resource utilization of CO2 is the fundamental way to solve the greenhouse effect and a series of environmental problems; at the same time, the problem of resource depletion will also be alleviated.

[0003] So far, many precious chemical raw materials have been synthesized using CO2 as raw material, such as urea derivatives, methane, formic acid, amides, dimethyl carbonate, cyclic carbonates, etc. Among them, cyclic carbonates have the characteristics of high boiling point, low toxicity, stable structure, etc., and are widely used in industrial production. Cyclic carbonates can be used as raw materials to synthesize polycarbonates, as solvents, they can be used for separation in traditional chemical industries, and can also be used as lithium battery electrolyte solvents, raw materials for engineering plastics, substitutes for toxic chemical reagents, and fine chemical intermediates. Due to the wide application of cyclic carbonates in industry, the efficient preparation of cyclic carbonates by epoxide cycloaddition is one of the important ways to utilize CO2.

[0004] In recent years, MOFs-based catalysts have been widely studied for catalyzing epoxides and CO2 to generate cyclic carbonates under uncatalyzed conditions. They can be mainly divided into three categories. The first category is some MOFs containing Lewis basic functional groups (such as -NH2, -NH, pyridine, etc.), which are generally contained in pre-designed organic ligands. For example, Dae-Won Park's research group used 2-aminoterephthalic acid, an organic ligand containing -NH2, to synthesize a MOFs catalyst, UMCM-1-NH2, which uses the basic site -NH2 to activate CO2 and catalyze the cycloaddition reaction of propylene oxide and CO2 under uncatalyzed conditions. Under the conditions of reaction temperature of 120 °C, CO2 pressure of 1.2 MPa, and reaction time of 24 h, the conversion rate of propylene oxide is 95% and the selectivity of propylene carbonate is 95%. The second type is to encapsulate ionic liquids or ionic polymers in the pores of neutral MOFs, and use the exposed Lewis acid sites in MOFs and the nucleophilic sites in the ionic liquids to promote the cycloaddition reaction of epoxide-CO2 to prepare cyclic carbonate reactions. For example, Jiang Hailong's research group prepared a composite material of polyILs@MIL-101 encapsulated in the pores of neutral MOFs. The polyionic liquid contains nucleophilic anions Br - , which can promote the activation of epoxides and avoid the addition of additional co-catalysts. The composite material was used to catalyze the cycloaddition reaction of epichlorohydrin and CO2. The yield of chloropropylene carbonate was 94% under the conditions of reaction temperature of 50°C and CO2 pressure of 0.1MPa for 24 hours. However, these two MOFs-based catalysts usually require a long reaction time in the cycloaddition reaction of epoxides and CO2.

[0005] The third category is ionic MOFs (IMOFs) with positively charged frameworks encapsulating anionic guests, which refers to the covalent bonding of cationic groups to the organic ligands of MOFs, so that the framework presents a net positive charge, and the pores contain counter anions (nucleophilic anions). Ionic MOFs with positively charged frameworks encapsulating anionic guests contain metal Lewis acid centers, which can activate epoxides by coordinating with the oxygen atoms of epoxides. The nucleophilic anions in the pores can attack the epoxides and promote their ring opening. The positively charged organic ligands can also be modified to activate CO2 or epoxides. They can catalyze the epoxide-CO2 cycloaddition reaction to prepare cyclic carbonates under uncatalyzed conditions, and are a multifunctional composite catalyst. Summary of the invention

[0006] The purpose of the present invention is to provide an ionic MOFs catalyst with an anionic guest wrapped in a positively charged framework, and to apply the catalyst to catalyze the cycloaddition reaction of epoxide-CO2 to prepare cyclic carbonate. The present invention grafts an ionic liquid onto sUiO-66-NH2 through a chemical bond to prepare a multifunctional heterogeneous catalyst, which is used to catalyze the cycloaddition reaction of epoxide-CO2 to prepare cyclic carbonate, has high activity and stability without using a co-catalyst, can effectively shorten the reaction time, and has multifunctionality and economy.

[0007] To achieve the above object, the present invention adopts the following technical solution: An ionic MOFs catalyst with a positively charged framework encapsulating an anionic guest, the preparation of which comprises the following steps: 1) 2-aminoterephthalic acid and ZrCl4 were dissolved in DMF, and then acetic acid was added. After ultrasonic treatment for 30 min, the mixed system was poured into a hydrothermal synthesis reactor for hydrothermal reaction. After the reaction was completed, the mixture was cooled to room temperature, and the obtained pink solution was immediately centrifuged and washed with an organic solvent and dried to obtain sUiO-66-NH2. 2) Slowly add HBr dropwise to triethylenediamine (DABCO), stir at room temperature for 12 h, remove water, and vacuum dry to obtain [DABCO][Br]; 3) Grinding the sUiO-66-NH2 obtained in step 1) and the [DABCO][Br] obtained in step 2) into powder, adding toluene to dissolve, and stirring the mixture under a nitrogen atmosphere; after the reaction, centrifugation, organic solvent washing, water removal, and vacuum drying are performed to obtain the ionic MOFs catalyst [D][Br]@sUiO-66-NH2 with the positively charged framework encapsulating the anionic guest.

[0008] Furthermore, the molar ratio of 2-aminoterephthalic acid and ZrCl4 used in step 1) is 1:2.

[0009] Furthermore, the molar ratio of 2-aminoterephthalic acid to acetic acid used in step 1) is 1:0.05.

[0010] Furthermore, the temperature of the hydrothermal reaction in step 1) is 110-130°C and the time is 72-74 h.

[0011] Furthermore, in step 1), the drying temperature is 50-70°C and the drying time is 12-14 h.

[0012] Furthermore, the mass ratio of triethylenediamine and HBr used in step 2) is 1:1.

[0013] Furthermore, the vacuum drying in step 2) is carried out at a temperature of 100-120°C and a time of 10-15 h.

[0014] Furthermore, the mass ratio of [DABCO][Br] and sUiO-66-NH2 used in step 3) is 1:1.

[0015] Furthermore, the stirring reaction in step 3) is carried out at a temperature of 90-100°C and for a time of 12-14 h.

[0016] Furthermore, the vacuum drying in step 3) is carried out at a temperature of 90-110°C and for a time of 12-14 h.

[0017] The obtained ionic MOFs catalyst with anionic guests encapsulated by a positively charged framework can be used to catalyze the cycloaddition reaction of epoxides and CO2 to prepare cyclic carbonates.

[0018] Furthermore, the epoxide includes any one of styrene oxide, epichlorohydrin, propylene oxide, butylene oxide and the like.

[0019] Furthermore, the cycloaddition reaction is carried out at a temperature of 100-120°C, a pressure of 1-1.2 MPa, and a time of 12-14 hours.

[0020] Styrene oxide molecules contain benzene rings, which have large steric hindrances, hindering the approach and reaction of CO2 and epoxy groups, which increases the activation energy of the reaction and increases the difficulty of the reaction; at the same time, because the benzene ring is an electron-rich group with an electron-donating conjugated effect, the electron cloud density of the epoxy group in styrene oxide increases, and the electrophilicity decreases, which is not conducive to the attack of the nucleophilic reagent CO2; therefore, the cycloaddition reaction of styrene oxide and CO2 has different characteristics from the cycloaddition of other systems, and the reaction is difficult. The present invention adopts a unique material structure design and component improvement method to provide an ionic MOFs catalyst. The catalyst exhibits two significant characteristics: first, a relatively considerable yield can be achieved in the process of cycloaddition reaction of styrene oxide and CO2 to prepare cyclic carbonates, which is significantly better than the material performance in the prior art; second, this catalyst has a wide range of applicability to the reaction of various epoxides with CO2, and can effectively promote the reaction and generate the corresponding cyclic carbonates.

[0021] The advantages and effects of the present invention are: 1. The present invention provides an ionic MOFs catalyst with a positively charged framework encapsulating anionic guests, which introduces ionic liquids into the MOFs structure, so that it has the ability to adsorb and activate CO2 and promote the ring opening of epoxides, thereby obtaining a multifunctional heterogeneous catalyst.

[0022] 2. When the ionic MOFs catalyst prepared by the present invention is used to catalyze the cycloaddition reaction of epoxides and CO2 to prepare cyclic carbonates, no additional co-catalyst and solvent are required, and the catalyst has a certain universality. When catalyzing the cycloaddition reaction of various epoxides and CO2, the conversion rate of epoxides is 100% and the selectivity of cyclic carbonates is greater than 80%. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 XRD comparison spectra of samples sUiO-66-NH2 and [D][Br]@sUiO-66-NH2 prepared in Example 1.

[0024] Figure 2 SEM comparison spectra of samples sUiO-66-NH2 (a) and [D][Br]@sUiO-66-NH2 (b) prepared in Example 1. DETAILED DESCRIPTION

[0025] An ionic MOFs catalyst with a positively charged framework encapsulating an anionic guest, the preparation of which comprises the following steps: 1) 2-aminoterephthalic acid and ZrCl4 are dissolved in DMF in a molar ratio of 1:1, and then acetic acid is added in a molar ratio of 0.05:1 to 2-aminoterephthalic acid. After ultrasonic treatment for 30 minutes, the mixed system is poured into a hydrothermal synthesis reactor and reacted in a forced air drying oven at 110-130 ° C for 72-74 hours; after the reaction is completed, it is cooled to room temperature, and the obtained pink solution is immediately centrifuged and washed with an organic solvent (the product is pink at this time. If the treatment time is too long, the product is light yellow and cannot be used), and then dried in a common oven at 50-70 ° C for 12-14 hours to obtain sUiO-66-NH2; 2) Weigh triethylenediamine (DABCO) in a beaker, then slowly add hydrogen bromide (HBr) in a mass ratio of 1:1 in a fume hood, stir at room temperature for 12 hours, place in a common oven to remove water, and then place in a vacuum oven at 100-120 ° C to dry for 10-15 hours to obtain [DABCO][Br]; 3) Grind the sUiO-66-NH2 obtained in step 1) and the [DABCO][Br] obtained in step 2) into powder, place them in a round-bottom flask at a mass ratio of 1:1, add toluene to dissolve, and stir the mixture in an oil bath at 90-100° C. for 12-14 h under a nitrogen atmosphere; after the reaction, centrifuge the obtained sample to separate the solvent, wash it with an organic solvent, place it in a common oven to remove water, and finally vacuum dry it in a vacuum drying oven at 90-110° C. for 12-14 h to obtain an ionic MOFs catalyst [D][Br]@sUiO-66-NH2 with a positively charged framework encapsulating an anionic guest.

[0026] In order to make the contents of the present invention easier to understand, the technical solution of the present invention is further described below in conjunction with specific implementation methods, but the present invention is not limited thereto. Example

[0027] 1) 2-aminoterephthalic acid (0.181 g, 1.0 mmol) and ZrCl4 (0.466 g, 2.0 mmol) were dissolved in DMF (60 mL), and then acetic acid (3.0 g, 0.05 mmol) was added. After ultrasonication for 30 minutes, the mixed system was poured into a 100 ml hydrothermal synthesis reactor and heated at 120 °C in a forced air drying oven for 72 h. Thereafter, the hydrothermal synthesis reactor was cooled to room temperature, the resulting pink solution was centrifuged and washed twice with DMF and methanol, respectively, and then dried at 60 °C for 24 h to obtain the Zr-based MOFs material sUiO-66-NH2.

[0028] 2) Weigh DABCO and HBr in a molar ratio of 1:1. Then place DABCO in a beaker, slowly drop HBr in a fume hood, stir the resulting mixture at room temperature for 12 hours, place it in a common oven to remove water, and then place it in a vacuum oven at 100°C to dry for 12 hours to obtain the ionic liquid [DABCO][Br].

[0029] 3) Grind 1 g of [DABCO][Br] and 1 g of sUiO-66-NH2 into powder and place in a 100 ml round-bottom flask, then add 50 ml of solvent toluene, place in a 95 °C oil bath and stir for 12 h. After the reaction, centrifuge the obtained sample to separate the solvent, wash it twice with DMF and methanol respectively, place it in a common oven to remove water, and finally place it in a vacuum drying oven at 100 °C to dry for 12 h to obtain the composite material [D][Br]@sUiO-66-NH2.

[0030] Figure 1 XRD comparison spectra of sUiO-66-NH2 and [D][Br]@sUiO-66-NH2 prepared in this example. It can be seen from the figure that after the ionic liquid [DABCO][Br] is immobilized on sUiO-66-NH2, the crystal form of sUiO-66-NH2 does not change, indicating that the introduction of [DABCO][Br] does not destroy the crystal structure of sUiO-66-NH2.

[0031] Figure 2The SEM comparison spectra of sUiO-66-NH2 and [D][Br]@sUiO-66-NH2 prepared in this example. It can be seen from the figure that the microscopic morphology of sUiO-66-NH2 is a regular octahedron (a), while after the introduction of [DABCO][Br], it still presents a regular octahedron shape (b), indicating that the introduction of [DABCO][Br] does not destroy the skeleton structure of sUiO-66-NH2.

[0032] Application Example 1 At room temperature, 2 mmol of epichlorohydrin and 5 wt.% of [D][Br]@sUiO-66-NH2 prepared in Example 1 were weighed in a parallel high-pressure reactor with a magnetic stirrer. The reactor was carefully sealed and purged with CO2 gas five times to remove the residual air in the reactor and the moisture in the atmosphere, and then filled with 1.0 Mpa of CO2, and the temperature was set to 100 °C, the reaction time was 12 h, and the speed was 300 rpm. After the reaction was completed, the reactor was cooled to room temperature, and the excess gas in the reaction vessel was slowly released until the reactor returned to normal pressure. After the reaction was completed, a gas chromatograph was used for quantitative analysis.

[0033] It was determined that under the above reaction conditions, the conversion rate of epichlorohydrin was 100% and the yield of allyl chloride carbonate was 95.17%.

[0034] Application Example 2 At room temperature, 2 mmol of propylene oxide and 5 wt.% of [D][Br]@sUiO-66-NH2 prepared in Example 1 were weighed in a parallel high-pressure reactor with a magnetic stirrer. The reactor was carefully sealed and purged with CO2 gas five times to remove the residual air in the reactor and the moisture in the atmosphere, and then filled with 1.1 Mpa of CO2, and the temperature was set to 110 °C, the reaction time was 14 h, and the speed was 400 rpm. After the reaction was completed, the reactor was cooled to room temperature, and the excess gas in the reaction vessel was slowly released until the reactor returned to normal pressure. After the reaction was completed, a gas chromatograph was used for quantitative analysis.

[0035] It was determined that under the above reaction conditions, the conversion rate of propylene oxide was 100% and the yield of propylene carbonate was 98.20%.

[0036] Application Example 3 At room temperature, 2 mmol of butylene oxide and 5 wt.% of [D][Br]@sUiO-66-NH2 prepared in Example 1 were weighed in a parallel high-pressure reactor with a magnetic stirrer. The reactor was carefully sealed and purged with CO2 gas five times to remove the residual air in the reactor and the moisture in the atmosphere, and then filled with 1.2 Mpa of CO2, and the temperature was set to 120 °C, the reaction time was 13 h, and the speed was 400 rpm. After the reaction was completed, the reactor was cooled to room temperature, and the excess gas in the reaction vessel was slowly released until the reactor returned to normal pressure. After the reaction was completed, a gas chromatograph was used for quantitative analysis.

[0037] It was determined that under the above reaction conditions, the conversion rate of butylene oxide was 100% and the yield of butylene carbonate was 92.32%.

[0038] Application Example 4 At room temperature, 2 mmol of styrene oxide and 5 wt.% of [D][Br]@sUiO-66-NH2 prepared in Example 1 were weighed in a parallel high-pressure reactor with a magnetic stirrer. The reactor was carefully sealed and purged with CO2 gas five times to remove the residual air in the reactor and the moisture in the atmosphere, and then filled with 1.2 Mpa of CO2, and the temperature was set to 100 °C, the reaction time was 14 h, and the speed was 400 rpm. After the reaction was completed, the reactor was cooled to room temperature, and the excess gas in the reaction vessel was slowly released until the reactor returned to normal pressure. After the reaction was completed, a gas chromatograph was used for quantitative analysis.

[0039] It was determined that under the above reaction conditions, the conversion rate of styrene oxide was 100% and the yield of styrene cyclic carbonate was 80.55%.

[0040] The above description is only a preferred embodiment of the present invention. All equivalent changes and modifications made according to the scope of the patent application of the present invention should fall within the scope of the present invention.

Claims

1. An ionic MOFs catalyst with a positively charged framework encapsulating anionic guests, characterized in that: Its preparation comprises the following steps: 1) 2-aminoterephthalic acid and ZrCl4 were dissolved in DMF, and then acetic acid was added. After ultrasonic treatment for 30 min, the mixed system was poured into a hydrothermal synthesis reactor for hydrothermal reaction. After the reaction was completed, the mixture was cooled to room temperature, and the obtained pink solution was immediately centrifuged and washed with an organic solvent and dried to obtain sUiO-66-NH2. 2) Slowly add HBr dropwise to triethylenediamine, stir at room temperature for 12 h, remove water, and vacuum dry to obtain [DABCO][Br]; 3) Grinding the sUiO-66-NH2 obtained in step 1) and the [DABCO][Br] obtained in step 2) into powder, adding toluene to dissolve, and stirring the mixture under a nitrogen atmosphere; after the reaction, centrifugation, organic solvent washing, water removal, and vacuum drying are performed to obtain the ionic MOFs catalyst with the positively charged framework encapsulating the anionic guest.

2. The ionic MOFs catalyst of claim 1, wherein: The molar ratio of 2-aminoterephthalic acid and ZrCl4 used in step 1) is 1:

2.

3. The ionic MOFs catalyst of claim 1, wherein: The molar ratio of 2-aminoterephthalic acid to acetic acid used in step 1) is 1:0.

05.

4. The ionic MOFs catalyst of claim 1, wherein: The temperature of the hydrothermal reaction in step 1) is 110-130°C and the time is 72-74 h.

5. The ionic MOFs catalyst of claim 1, wherein: The mass ratio of triethylenediamine and HBr used in step 2) is 1:

1.

6. The ionic MOFs catalyst of claim 1, wherein: The mass ratio of [DABCO][Br] and sUiO-66-NH2 used in step 3) is 1:

1.

7. The ionic MOFs catalyst of claim 1, wherein: The stirring reaction in step 3) is carried out at a temperature of 90-100°C and for a time of 12-14 h.

8. Use of the ionic MOFs catalyst comprising a positively charged framework encapsulating anionic guests as claimed in claim 1 in catalyzing the cycloaddition reaction of epoxides and CO2 to prepare cyclic carbonates.

9. The use according to claim 8, characterized in that: The epoxide includes any one of styrene oxide, epichlorohydrin, propylene oxide and butylene oxide.

10. The use according to claim 8, characterized in that: The cycloaddition reaction is carried out at a temperature of 100-120°C, a pressure of 1-1.2 MPa and a time of 12-14 h.

Citation Information

Patent Citations

  • Ionic MOFs material and preparation method thereof and application in preparation of cyclic carbonate

    CN112979984A

  • Method for preparing cyclic carbonate catalyst through carbon dioxide cycloaddition reaction

    CN117718079A

  • Lens driving device

    KR102212890B1

  • A Recording medium on which repeater data transmission / reception program of DisplayPort side channel is recorded

    KR102712668B1

  • Two-dimensional catalytic materials derived from metal-organic frameworks for VOC remediation

    US20200094187A1